A systematic review and meta-analysis on the quality of life after hepatic resection. Issue 2 (February 2020) - Wee, Ian J.Y.; Syn, Nicholas; Lee, Lip Seng; Tan, Siong San; Chiow, Adrian K.H.
Abstract: Background: Quality of life (QoL) after hepatic resection is a pertinent issue that has been poorly studied. The aim of this study was to compare changes in QoL before and after hepatic resection. Methods: A systematic review was performed using Medline, EMBASE, and the Cochrane library. Whenever possible, pooled mean differences of survey scores pre- and post-operatively were calculated. Results: 22 studies were included comprising a total of 1785 participants. Using the EORTC-QLQ 30C survey, patients with benign disease tend to have better QoL post-surgery than those with malignant disease. There were post-operative improvements in the following FACT-HEP domains: physical at 9 months (MD 3.14, 95%CI 2.70 to 3.58, P < 0.001), social and family at 3 (MD 1.45, 95%CI 0.12 to 2.77, p = 0.030), 6 (MD 1.12, 95%CI 0.21 to 2.04, p = 0.020), 9 (MD 0.66, 95%CI 0.03 to 1.28, p = 0.040), and 12 (MD 0.58, 95%CI 0.12 to 1.03, p = 0.010) months, emotional at 9 (P < 0.001) and 24 months (P < 0.001), hepatobiliary at 24 months (p < 0.001), and global health status at 9 months (p = 0.002). Conclusion: QoL scores tend to deteriorate post-surgery, but recover to baseline in the long-term at 9-months. Patients with malignant disease, and those who underwent major hepatectomy, have poorer QoL scores.